Comparison of Public Service Organizations in Bintan Regency and Tanjungpinang City: An Analysis of Bureaucratic Role Conflict in the Implementation of Sustainable Public Policies - F. Firman; Harapan Tua; Rafika Duri; Barlian Erliadi (Manunggal Halim Jaya, 2026)
This study aims to analyze the comparative nature of public service organizations in Bintan Regency and Tanjungpinang City, emphasizing the role conflict between bureaucrats in implementing sustainable public policies. Public organizations play a crucial role as policy implementers, transforming government decisions into public services. However, in practice, role conflict often occurs due to abuse of authority, unclear division of tasks, and differing interests among bureaucratic institutions. This study applies a qualitative approach and descriptive explanatory analysis methods to observe the differences in the characteristics of public service organizations in the two regions. The research findings indicate that variations in organizational structure, bureaucratic capacity, and regional development focus influence the dynamics of role conflict in public policy implementation. Bintan Regency, which focuses on developing the tourism sector, faces challenges in inter-agency coordination related to development policies, while Tanjungpinang City, as the center of government administration, experiences complex bureaucratic coordination for public services. This study explains the significance of role clarity, inter-institutional collaboration, and increasing the capacity of bureaucratic organizations to improve the effectiveness of public policy implementation and the quality of services to the public.